2007
DOI: 10.1002/bsl.783
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of the Dutch PCL:YV for institutional disruptive behavior: findings from two samples of male adolescents in a juvenile justice treatment institution

Abstract: The present prospective study examined the predictive validity of the Dutch version of the Psychopathy Check List: Youth Version for disruptive behavior in male adolescents during treatment. The study comprised two samples admitted to different secure treatment institutions in The Netherlands, Jongerenhuis Harreveld (n = 81) and Rentray (n = 66). Overall, the results demonstrate that psychopathy is a significant predictor of institutional disruptive behavior, and physical violence in particular. Furthermore, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 39 publications
(52 reference statements)
2
21
0
2
Order By: Relevance
“…Concluding, with respect to the stability and concurrent and prospective associations between self-reported psychopathic traits and conduct problems and aggression, our findings confirm past findings in both adolescents (e.g. Andershed et al 2002, Campbell et al 2004Das et al 2007;Marsee et al 2005;Pardini and Loeber 2008) and children using teacher and parent report (Christian et al 1997;Dadds et al 2005;Hawes and Dadds 2007;Lynam 1997).…”
Section: Discussionsupporting
confidence: 90%
“…Concluding, with respect to the stability and concurrent and prospective associations between self-reported psychopathic traits and conduct problems and aggression, our findings confirm past findings in both adolescents (e.g. Andershed et al 2002, Campbell et al 2004Das et al 2007;Marsee et al 2005;Pardini and Loeber 2008) and children using teacher and parent report (Christian et al 1997;Dadds et al 2005;Hawes and Dadds 2007;Lynam 1997).…”
Section: Discussionsupporting
confidence: 90%
“…These findings merit further investigation since, there is a well‐documented connection between anxiety and antisocial behaviour in children and adolescents (Frick, Lilenfeld, Ellis, Loney, & Silverthorn, 1999). Previous studies have suggested a positive association between the behavioural dimension of psychopathy and anxiety among males (Das, de Ruiter, Lodewijks, & Doreleijers, 2007; Mailloux, Forth, & Kroner, 1997) as well as a negative association between the behavioural as well as the affective dimension and anxiety among males (Dolan & Rennie, 2007; Hale, Goldstein, Abramowitz, Calamari, & Kosson, 2004).…”
mentioning
confidence: 97%
“…In addition to the non-representativeness, the method of recruitment of participants was unclear, or flawed in some of the studies. In five studies, it was not clear how participants were recruited (Das et al, 2007;Miller et al, 2010;Verona et al, 2012-Study 1 and Study 2;Witt et al, 2010). One study did not report how many participants did not give consent, or were excluded (Negredo et al, 2013).…”
Section: Section 1: Populationmentioning
confidence: 99%
“…In two of the studies, participants were men being assessed for suitability for the Turkish military (Ates et al, 2011;Swogger et al, 2009 (Das et al, 2007). The PCL:JV has been shown to be less reliable and have lower inter-rater reliability than the PCL:YV (Das, de Ruiter, & Doreleijers, 2008), and therefore this measure of psychopathy is likely to be less valid and reliable than the PCL-R and PSL:SV, which was used in other studies.…”
Section: Section 1: Populationmentioning
confidence: 99%
See 1 more Smart Citation